Un compás que hace cuadrados: La escritura y la lectura en el currículum de séptimo año en Costa Rica - Ramírez Molina, Catalina (Universidad de Costa Rica, 2018)
This article presents the results of an in-depth analysis of the curricular document of reading and writing areas of the first year of high school Program of Studies in Costa Rica, using the systemic networks approach. The purpose is to know firstly, the contents of the curricular text regarding these two areas. Secondly, there is a contrast between the results of the analysis and the new didactic conceptions for the teaching of language and literature. The analysis reveals a curricular proposal lacking of didactic knowledge, which guides the practices of writing and reading in secondary school. Therefore, some changes are suggested as a curricular proposal that allows teachers to plan a coherent program that assures their students the appropriation of a literacy in harmony with the development of reading and writing skills necessary to live today.